Assessing post-fire tree regeneration and forest conversion across an elevational gradient in southern Colorado - Hastings, Amanda K., author; Stevens-Rumann, Camille, advisor; Fornwalt, Paula, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2023)
Increased wildfire activity, with anticipated novel climate scenarios, raises concerns about forest resilience—particularly in semi-arid regions of the western US. Specifically in southwestern US and Southern Rocky Mountain forests, lack of conifer seed sources and shifts in temperature or precipitation post-wildfire may limit the recruitment of dominant conifer species. Meanwhile, hotter and drier conditions may promote the proliferation of resprouting angiosperm species, resulting in vegetative type conversions. To better understand forest susceptibility to type conversion following wildfire, I assessed early vegetation assembly 3 years post-fire, in sites that burned at low and high severity and spanned a climatic gradient in the Sangre de Cristo range of southern Colorado. Research sites were located in lower montane, upper montane, and subalpine forests, with relative dominances of Pinus ponderosa- Pseudotsuga menziesii; Abies concolor- Pinus contorta- Populus tremuloides; and Abies lasiocarpa- Picea engelmannii- Pinus flexilis- Pinus aristata; respectively. I quantified post-fire tree seedling densities and other site-specific attributes to evaluate a) how do burn severity and forest type influence early post-fire tree regeneration, b) are these forest types undergoing conversions? and c) if so, what factors are driving type-conversion?In this early assessment, I found concerns of forest conversion may be warranted for lower montane forests, with greater abundances of deciduous tree-shrub species, Quercus gambelii and Robinia neomexicana, and high shrub cover. Meanwhile, upper montane forests are likely regenerating to a similar forest composition, with early Populus tremuloides dominance and Pinus contorta regeneration. For both lower and upper montane forest types, conifer regeneration was positively correlated with legacies of low-moderate severity fire, such as overstory cover and litter/woody debris. Meanwhile, subalpine tree regeneration was driven by site-climate and topographic position, regardless of fire severity. In subalpine forests, this study suggests early post-fire conifer regeneration may be dominated by xeric and drought-tolerant species, Pinus flexilis, Pinus aristata, and Pinus contorta, where decades may pass before the establishment of shade-tolerant species characteristic of this forest type. Across all forest types, greater time is required in the post-fire period to predict ultimate recovery trajectories. However, this study serves as one of the first within southern Colorado to evaluate post-fire regeneration across a full elevational gradient and multiple forest types within a single fire footprint.
Keywords: disturbance; fire ecology; wildfire; elevation gradient; conversion; regeneration